(untitled) (Chemical Engineering Research Bulletin, 2008)
Air pollution is one of the major environmental problems now days, especially for developing countries such as Bangladesh and Brickfields have been identified as a vital pollutant source of the major cities of the country. Verification of the applicability of an effective air quality model in Bangladesh condition, especially for brickfield pollution was the main concern of this work. To achieve that objective, ambient pollutant concentrations were measured experimentally and compared with the results generated through modeling using Industrial Source Complex (ISC3) model. Air sampling was done at different locations in a cluster of brickfields of 41 brick kilns near Amin Bazar, Savar using Gastec tubes and High volume sampler. Gastec tubes were used for gaseous pollutants and High volume sampler was used for Total Suspended Particulates (TSP). Gaseous pollutants included Sulfur dioxide, Carbon monoxide, and Hydrocarbons. Those pollutant data at different locations on different days were compared with simulated value generated through ISC3. Industrial Source Complex (ISC3) model was found very effective and appropriate both for gaseous pollutants and particulate matter for brickfield pollution in Bangladesh and which indicates the prospect of utilizing this model for different condition and purposes in Bangladesh. From both the experimental and simulated data, particulate matter had been identified as the most important pollutant in that region which is urgently needed to be taken care of. Keywords: Air pollution, Brickfield, Gaussian Plume, ISC, Modeling. DOI = 10.3329/cerb.v12i0.1495 Chemical Engineering Research Bulletin 12 (2008) 28-34